Construction of a pillararene-based supramolecular polymer network and its application in efficient removal of dyes from water. Issue 3 (22nd December 2021) - Lv, Xiaoqing; Xia, Danyu; Cheng, Yujie; Chao, Jianbin; Wei, Xuehong; Wang, Pi
Abstract : A new supramolecular polymer network based on pillararene was constructed and its application in efficient removal of dyes from water was studied. Abstract : An AB-type monomer based on a pillar[5]arene host and an imidazolium salt guest was successfully synthesized through a facile way. This monomer can self-assemble into linear supramolecular polymers in chloroform. After the addition of silver ions, the imidazolium salt group coordinated with silver ions to crosslink the linear supramolecular polymers at their ends, resulting in the formation of supramolecular polymer networks. Meanwhile, after further adding iodide ions, the supramolecular polymer network changed back to the linear supramolecular polymer. As a result, the topological structure of the system can be reversibly tuned. Furthermore, this supramolecular polymer network can be applied to remove organic dyes in water, suggesting its great potential in the treatment of waste water.